2016
DOI: 10.1002/icd.2009
|View full text |Cite
|
Sign up to set email alerts
|

The role of fantasy–reality distinctions in preschoolers' learning from educational video

Abstract: The current study examined if preschoolers' understanding of fantasy and reality are related to their learning from educational videos. Forty‐nine 3‐ to 6‐year‐old children watched short clips of popular educational programs in which animated characters solved problems. Following video viewing, children attempted to solve real‐world problems analogous to the problems in the videos and were asked to describe similarities between the video problems and the problems they solved in the lab. Additionally, children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 55 publications
1
22
1
2
Order By: Relevance
“…Several studies have shown that engaging in active fantasy-oriented play or fantastical pretense may directly enhance preschool children's EF development (Thibodeau-Nielsen et al, 2016;Thibodeau-Nielsen et al, 2020). By turning toward EF, these studies extended earlier findings showing that magical or impossible events in film (Subbotsky et al, 2010;Richert and Schlesinger, 2016) and the exercise of imagination (Bunce et al, 2017) may facilitate preschoolers' creative thinking. With this acknowledgment, we turn to the relations between screen time and EF in preschoolers.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Several studies have shown that engaging in active fantasy-oriented play or fantastical pretense may directly enhance preschool children's EF development (Thibodeau-Nielsen et al, 2016;Thibodeau-Nielsen et al, 2020). By turning toward EF, these studies extended earlier findings showing that magical or impossible events in film (Subbotsky et al, 2010;Richert and Schlesinger, 2016) and the exercise of imagination (Bunce et al, 2017) may facilitate preschoolers' creative thinking. With this acknowledgment, we turn to the relations between screen time and EF in preschoolers.…”
Section: Introductionsupporting
confidence: 71%
“…Although more than 70% of these studies found a negative association between television viewing and children's attention quality, such evidence may be inadequate without placing children in their social context and taking into account other factors that could affect attention (Kostyrka-Allchorne et al, 2017). Close-to-real-life fantastical contents or contextualized fantasy in a TV program can facilitate preschoolers' performance on cognitive tasks (Richert and Schlesinger, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skill in fantasy-reality discrimination may support children in realizing that problem solutions in fantastical contexts may apply to real world problems. In support of this interpretation, Richert and Schlesinger ( 2016 ) found that 3- to 6-year-old children with a better understanding of the fantasy-reality distinction were better able to learn and transfer problem solutions from video stories when fantastical elements were present and relevant to the solution being presented. Fantastical elements that were incidental appeared to distract children and interfere with transfer.…”
Section: Domains Of Learningmentioning
confidence: 93%
“…The preschool years are filled with situations in which children must navigate between real and fantastic information through their play, imagination, and reading storybooks. Research shows that children can do this well and develop a sophisticated understanding of fantasy and reality (Richert & Schlesinger, ; Skolnick & Bloom, ; Woolley & Ghossainy, ). Yet when the information is emotionally charged, children can make fantasy–reality distinction errors (Gjersoe, Hall, & Hood, ; Harris, ; Samuels & Taylor, ), and specifically, children's reports of whether an event can happen in real life vary depending on the discrete emotion.…”
Section: Introductionmentioning
confidence: 99%